PENGARUH TEKNIK RELAKSASI OTOT PROGRESIF TERHADAP TINGKAT KECEMASAN PASIEN PRE OPERASI DENGAN ANASTESI SPINAL DI RAWAT INAP BEDAH RSU KOTA TANGERANG SELATAN TAHUN 2017 - Lisna Agustina; Fitri Hasanah (Jurnal Kesehatan STIKes IMC Bintaro, 2018)
Preoperation is an early stage of perioperative care that begins when the patient decides to take surgery to the operating table. Surgery is a potential and actual threat to one's integrity and can cause physiological and psychological stress reactions or anxiety. Nonpharmacological therapy is one of prevention and complementary therapies to reduce anxiety levels in preoperative patients with spinal anesthesia. This study aims to determine the effect of progressive muscle relaxation technique on preoperative patient anxiety level. This research methodology uses experimental quasy design with pretest posttest design with non equivalent control group. The sampling technique was done by purposive sampling obtained 58 respondents divided into intervention group and control group. The result of t-test analysis showed that there was difference of anxiety level of pre-post test in intervention group (p = 0,000 / p = 0,05) so Ha accepted and Ho rejected, but there was no difference of anxiety level in control group (p = 0,307 / p => 0.05) then Ho is rejected. The conclusion of this study is that there is an effect of progressive muscle relaxation techniques on anxiety levels in preoperative patients with spinal anesthesia. It is recommended for health providers and respondents to prevent the occurrence of anxiety levels in patients who will perform the operation and as complementary therapies in addition to medical therapy with an effective and economical method.